KONTRUKSI UALNG REAKTOR BIOGAS MENGGUNAKAN METODE REVERSE ENGINEERING - Sukirman Sukirman (Teknoin, 2014)
Increasingly high demand for fuel oil and gas to encourage people to look for alternative renewable fuels. The purpose of this paper is to present the results of redesigning the biogas reactor. This tool can be used to produce biogas from livestock manure into energy alternatives. Redesign was done due to the initial reactor construction, yet provide optimal results. Analysis carried out on parts of the construction that needs to be fixed, then redesign done by means of the duplicate revers engineering and develop existing ones. The result of this redesign later in the simulation with the help of software with tuuan to determine the output results are given. The results of the simulation showed that the redesign of the construction of a biogas reactor output that can add more gas from the biogas reactor construction that has been there for 4 kg or produce a pressure of 0,127psi in the morning, while the afternoon of 2 kg or produce a pressure of 0,090 psi of tank which has been used as a digester.